Tumor development in relatives of Lynch syndrome probands diagnosed via universal tumor screening - Ishida, Hideyuki; Suzuki, Okihide; Nagai, Tomonori; Kagawa, Makoto; Kamae, Nao; Fukuda, Tomoo; Minabe, Toshiharu; Eguchi, Hidetaka; Ito, Tetsuya; Okazaki, Yasushi; Kawakami, Satoru; Mori, Yoshiko; et al. (Journal of Hereditary Tumors, 2022)
There are few data on tumor development in relatives of Lynch syndrome (LS) probands in Japan. The aim of this retrospective study is to investigate the prevalence of LS-associated tumors in relatives of LS probands identified via universal tumor screening (UTS). Nineteen patients were diagnosed as having LS via UTS by immunohistochemical staining for DNA mismatch repair proteins of 2,141 tumors; including colorectal, endometrial, ovarian, upper urinary tract urothelial, and small-bowel cancers. We investigated the family tumor history of first-degree relatives (FDRs), second-degree relatives (SDRs), and third-degree relatives (TDRs) from 14 out of the 19 LS patients. There were 165 relatives (80 females); 58 FDRs，89 SDRs，and 18 TDRs. 39 relatives had 46 malignant tumors, of which 39 were LS-associated in 32 relatives. 31% (18/58) of FDRs, 11% (10/89) of SDRs, and 22% (4/18) TDRs had LS-associated tumors. Among FDRs and TDRs who had the tumors, tumor development was frequently seen in uterus (37% of females) colorectum (34%), and stomach (19%). FDRs in the older generation had significantly higher prevalence of LS-associated tumors compared with those in the younger or the same generation (FDRs：46 % vs 19%，P=0.04). The main sites of tumor development in relatives of LS were uterus, colorectum, and stomach in our study. In clinical practice for patients suggestive of LS, it seems important to take information about the medical history of their older generations.